Approximate Solutions of Singular Two-Point BVPs Using Legendre Operational Matrix of Differentiation - A. Sami Bataineh; A. K. Alomari; I. Hashim (Journal of Applied Mathematics)
Exact and approximate analytical solutions of linear and nonlinear singular two-point boundary value problems (BVPs) are obtained for the first time by the Legendre operational matrix of differentiation. Different from other numerical techniques, shifted Legendre polynomials and their properties are employed for deriving a general procedure for forming this matrix. The accuracy of the technique is demonstrated through several linear and nonlinear test examples.